The problem of exchange rate appreciation: theoretical and practical considerations - Fernández-Baca, Jorge (1990)
​This article considers the prospects for constructing a theoretical framework that allows the author understand the trend of the real exchange rate in Peru since 1989. After discarding the Purchasing Power Parity approach, because of its theoretical flaws and the portfolio approaches, because of their short-run emphasis, the author states the need for a real approach. Based on the Dornbusch, Fischer and Samuelson model he proposes an explanation in term of the interrelation between the sectors producing tradeables and non tradeables goods.